Modulation of insulin secretion and lipid profiles through glutamate dehydrogenase activators in diabetic rabbits - Abdreshov Serik Nauryzbaevish; Galiya Tatarinova; Oxikbayev Berikzhan; Amantai Kunakbayev4; Gulnara Tashenova; Atanbaeva Gulshat Kapalbaevna; Kulbayeva Marzhan Susarovnalbayeva; Shynybekova Sholpan (Caspian Journal of Environmental Sciences)
Diabetes mellitus is a prevalent metabolic disorder characterized by impaired insulin secretion and aberrant lipid metabolism. Targeting glutamate dehydrogenase (GDH) activators has emerged as a potential therapeutic strategy in managing diabetes. This study aims to investigate the effects of GDH activators on insulin secretion and lipid profiles in diabetic rabbits. Utilizing Streptozotocin (STZ) to induce diabetes in male New Zealand White rabbits, the impacts of three different GDH activators—Metformin, Epigallocatechin Gallate (EGCG), and Leucine—were examined. The subjects were categorized into five groups, including a diabetic control, a sham group, and three treatment groups administered with Metformin (5 mg kg-1), EGCG (15 mg kg-1), and Leucine (15 mg kg-1), respectively. The study reveals significant modulations in insulin and lipid profiles due to these treatments. In the Metformin-treated group, blood glucose levels significantly decreased during the second (p < 0.001) and third (p<0.01) weeks. The EGCG group exhibited a significant increase in insulin levels (p < 0.001), but no notable change in blood glucose. Conversely, the Leucine group showed an increase in triglyceride levels (p < 0.05) and a significant decrease in blood glucose levels (p < 0.01). Additionally, Metformin led to a substantial reduction in triglycerides (p < 0.001), while EGCG and Leucine were effective in lowering LDL levels (p < 0.01). Cholesterol and HDL levels remained relatively unchanged across all groups. These findings suggest that GDH activators, i.e., Metformin, EGCG, and Leucine, significantly impact insulin secretion and lipid metabolism, offering novel insights into diabetes management. This study not only demonstrates the therapeutic potential of these agents, but also emphasizes the importance of GDH pathways in diabetes research, providing a foundation for future investigations into metabolic regulation and treatment.